Chemical disinfectants of COVID-19: an overview - Al-Sayah, Mohammad (2020)
The outbreak of coronavirus (COVID-19) has led to a broad use of chemical disinfectants in order to sterilize public spaces and prevent contamination. This paper surveys the chemicals that are effective in deactivating the virus and their mode of action. It presents the different chemical classes of disinfectants and identifies the chemical features of these compounds that pertain to their biocidal activity, relevant to surface/water disinfection.